The Epithelial-Immune Crosstalk in Pulmonary Fibrosis - Planté-Bordeneuve, Thomas; Pilette, Charles; Froidure, Antoine (Frontiers in Immunology, 2021)
Interactions between the lung epithelium and the immune system involve a tight regulation to prevent inappropriate reactions and have been connected to several pulmonary diseases. Although the distal lung epithelium and local immunity have been implicated in the pathogenesis and disease course of idiopathic pulmonary fibrosis (IPF), consequences of their abnormal interplay remain less well known. Recent data suggests a two-way process, as illustrated by the influence of epithelial-derived periplakin on the immune landscape or the effect of macrophage-derived IL-17B on epithelial cells. Additionally, damage associated molecular patterns (DAMPs), released by damaged or dying (epithelial) cells, are augmented in IPF. Next to “sterile inflammation”, pathogen-associated molecular patterns (PAMPs) are increased in IPF and have been linked with lung fibrosis, while outer membrane vesicles from bacteria are able to influence epithelial-macrophage crosstalk. Finally, the advent of high-throughput technologies such as microbiome-sequencing has allowed for the identification of a disease-specific microbial environment. In this review, we propose to discuss how the interplay between the altered distal airway and alveolar epithelium, the lung microbiome and immune cells may shape a pro-fibrotic environment. More specifically, it will highlight DAMPs-PAMPs pathways and the specificities of the IPF lung microbiome while discussing recent elements suggesting abnormal mucosal immunity in pulmonary fibrosis.